Primary cosmic ray electrons and albedo electrons in 1967 at energies between 12 and 1000 MEV - Israel, Martin Henry (California Institute of Technology, 1969)
NOTE: Text or symbols not renderable in plain ASCII are indicated by [...]. Abstract is included in .pdf document. We measured the flux of cosmic ray electrons in a series of high altitude balloon flights. Balloons launched from Fort Churchill, Manitoba,on 17 June, 2 July, 9 July, and 21 July, 1967, floated near 2 g/cm[superscript 2] atmospheric depth; and one launched from Palestine, Texas on 7 April, 1967, floated near 5 g/cm[superscript 2]. The detector system included a threshold gas Cerenkov counter, a digital spark chamber with lead plates, and scintillation counters. During the flight of 9 July, the detector was pointed toward the nadir to observe the splash albedo. We present the resulting energy spectrum and also the return albedo spectrum observed in the April flight. In the other three flights, we observed the diurnal variation near the polar cap of the flux of downward-moving electrons with energy [.....] 100 MeV. The nighttime flux is significantly lower than the splash albedo, while the daytime flux is in good agreement with the splash albedo. This comparison lends strong support to the model in which the low nighttime flux consists of primary electrons and atmospheric secondaries, while in the daytime the primaries are replaced by return albedo. We find that the nighttime geomagnetic cutoff near 68[degrees] geomagnetic latitude is below 17 MV, and the daytime cutoff is between 70 and 110 MV. Making use of our analysis of the diurnal variation, we examine the primary electron spectrum. The observed flux of electrons with energy above the local geomagnetic cutoff and below 350 MeV is consistent with the expected flux of atmospheric secondaries; we derive 2[...] upper limits to the primary electron flux of 20, 9, and 13 electrons/m[superscript 2] sec sr in the intervals 17-57, 57-112, and 112-374 MeV respectively. We find 16 [plus or minus] 14 electrons/m[superscript 2] sec sr between 374 and 1060 MeV. Comparison between the observed primary flux and the calculated flux of galactic secondary electrons indicates an absolute solar modulation of electrons below 100 MeV by at least a factor of three.